Creativity, culture and urban development: Toronto examined. - Miles, Simon (TH Zürich, ORL-Institut, 2005)
Der Beitrag zeigt zunächst die Zusammenhänge zwischen Kreativität, Kultur und Stadtentwicklung auf und formuliert Konsequenzen für eine erfolgreiche Stadtentwicklungsplanung. Der zweite Teil des Beitrags beschäftigt sich mit der kanadischen Metropole Toronto unter vier Aspekten: Kreativität und Governance; Kreativität, Wissen und Information; Kultur; Kreativwirtschaft, Stadtentwicklung und kreative Räume. Stärken und Schwächen der Stadt werden analysiert und zeigen Toronto als einen Ort von höchster Lebensqualität, an dem ein kulturelles Klima für Kreativität geschaffen und gefördert wird. oc/difu

The paper is driven by the desire to provide public policy makers with: first, a context for the debate on the links between creativity, culture and urban development; and, second, some guidance on the shaping of decisions of consequence for society. The author elaborates a conceptual model of the process of human and societal development, and then looks at creativity and cities, and the meanings of culture. To satisfy the second objective, the author provides an analysis of the City of Toronto structured around four themes: creativity and governance; creativity, knowledge and information; culture, creative industries and urban development; and creative spaces in urban development. The City's strengths and shortcomings are assessed, giving the reader a sense of how well Toronto is performing as a setting that is enabling of creativity and fostering a cultural environment that is contributing to an improved quality of life. difu
Keywords: Stadtentwicklungsplanung; Kultur; Planungstheorie; Lebensqualität; Kooperation; Stadtgesellschaft; Kreativität; Governance; Kreativwirtschaft; Kulturwirtschaft; Urban Governance